Aplicação de ensaios não destrutivos magnéticos para caracterização da junta soldada de aço inoxidável duplex UNS S31803 - Coelho, Lucas Mirandola (2022)
The evaluation of the percentage of phases, hardness and residual stress of the weld bead and of the thermally affected zones of the duplex stainless steel UNS S31803 (SAF 2205) through non-destructive magnetic techniques is the main objective of this work. For this, four sheets of duplex stainless steel UNS S31803 (SAF 2205) with a thickness of 1.8 mm were welded, by the GTAW (TIG) process, with four different energy levels to evaluate the thermally affected zone 5 mm away from the bead. weld and heat-affected zone 10 mm away from the weld bead. The results revealed an increase in ferrite content and a decrease in weld bead hardness with increasing welding energy, in addition to higher levels of residual stress in the weld bead compared to the heat-affected zones. Regarding the Barkhausen magnetic noise, an increase in the RMS value was observed in the molten zone with the increase in welding energy, which is accompanied by an increase in the ferrite content and a decrease in hardness. In addition, the RMS signal presented higher values for the longitudinal direction, that is, parallel to the welding direction, following the highest residual stress values, which were also calculated in the longitudinal direction. Finally, in relation to the eddy current technique, it was noted that, in general, the highest values for the phase angle were calculated for the molten zone, where the percentages of ferrite and the residual voltage levels presented higher values and the hardness levels were lower.